2018
DOI: 10.1001/jamapsychiatry.2018.1924
|View full text |Cite
|
Sign up to set email alerts
|

Reward System Abnormalities in Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is associated with the highest mortality rate of any psychiatric illness 1 as well as significant health care costs and lost wages. While there have been notable advances in understanding biobehavioral mechanisms of AN, the brain systems that underlie the illness remain poorly understood. Clinically, it is widely accepted that the critical first step in treatment is renourishment-that is, restoring individuals to a healthy body weight. Yet knowing that the primary medical intervention is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…In line with previous literature findings, our AN patients presented a lower mood baseline and a higher EMSs score compared with HCs (Damiano et al, ; Meehan, Loeb, Roberto, & Attia, ). This is consistent with previous literature that showed how AN patients present a specific temperamental, cognitive, and behavioural profile with a rigid approach to changes that can affect a mild, flexible mind state as well as their connection with feelings and emotions (Duffy et al, ; Kaye et al, ; Oldershaw, Startup, & Lavender, ; Steinglass & Foerde, ). The literature has already shown that the AN patients present lower self‐esteem, higher fear of negative evaluation, and higher social physical comparison than controls, which are feelings that can affect social relationships (Cardi et al, ; Duarte, Ferreira, & Pinto‐Gouveia, ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous literature findings, our AN patients presented a lower mood baseline and a higher EMSs score compared with HCs (Damiano et al, ; Meehan, Loeb, Roberto, & Attia, ). This is consistent with previous literature that showed how AN patients present a specific temperamental, cognitive, and behavioural profile with a rigid approach to changes that can affect a mild, flexible mind state as well as their connection with feelings and emotions (Duffy et al, ; Kaye et al, ; Oldershaw, Startup, & Lavender, ; Steinglass & Foerde, ). The literature has already shown that the AN patients present lower self‐esteem, higher fear of negative evaluation, and higher social physical comparison than controls, which are feelings that can affect social relationships (Cardi et al, ; Duarte, Ferreira, & Pinto‐Gouveia, ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the model 245 did not uncover a group difference in a feedback sensitivity parameter, the finding that patients 246 tended to base their decisions on recent experience is commensurate with our finding of increased 247 learning rate in AN. The current evidence of altered decision-making in response to negative 248 feedback is in line with notion of altered reinforcement learning in AN (1)(2)(3)(4)(5)8) and, considered in 249 light of similar recent findings (13), is suggestive of a particular sensitivity to punishment. Decision-250 making may be intact, however, in paradigms that don't include negative feedback, at least in 251 adolescents (19,59).…”
Section: Imaging Data 187supporting
confidence: 82%
“…We only included participants who were weight stable (<3 kg weight change) and physiologically and cognitively remitted from AN for at least one year, and we systematically monitored and manipulated pre-scan nutritional status. In terms of limitations, the passive task was designed specifically to characterize differences in hard-wired circuitry underlying neural sensitivity to gustatory processing, limiting our ability to assess top-down cognitive control, decision-making, or learning 46 . Unexpectedly, all participants rated the water as more pleasant-tasting than the sucrose solution and both the water and sucrose solutions as moderately pleasant-tasting.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%